IN THE EXPERIENCE OF UZBEKISTAN AND FOREIGN COUNTRIES, THE ADDITION OF A SYSTEM OF OIL HOLDERS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In this article, the theoretical foundations, technological features and practical application of the system of oil holders were analyzed on the basis of the experience of Uzbekistan and foreign countries. The problems of cleaning oil and oil wastewater generated in the food industry, catering enterprises and production facilities are relevant from the point of view of environmental safety, uninterrupted operation of sewage systems and protection of Water Resources. The article covers the structural structure of oil holders, the principle of operation, regulatory framework and maintenance requirements. Also, on the basis of the experience of developed countries, specific aspects of modern technological solutions, automated systems and environmental requirements were analyzed. As a result of the study, scientific and practical recommendations for improving the system of oil holders in the conditions of Uzbekistan were developed.
Keywords: Oil holder, mechanism, wastewater, oil and oil substances, sewerage system, environmental safety, catering enterprises, foreign experience, rakovina, restaurants, fast food, confectionery shops, Uzbekistan practice.